Pengembangan Media Pembelajaran Berbasis Android Subtema 1 Keberagaman Budaya Bangsaku pada Kelas IV SD/MI - Budi, Irwan Setia; Kholik, Abd.; Abidin, Zainal (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to determine the level of success of students' interest in learning when using Android-based learning media in subtopic 1 learning outcomes of the Cultural Diversity of My Nation. . The subjects of this research were at MI Al Falah 1 Kadur Pamekasan. The subjects of this research were Class IV students at MI Al Falah 1 Kadur Pamekasan. The results showed that the use of interactive and live video learning materials had an impact on the learning outcomes of subtopic 1 about the cultural diversity of my society. This can be seen after the t test was carried out. We can all know that the final result of checking the product is to get t_count = 2.954, namely left check, so t_count = 2.954 > t_table = 1.710 whereas ????0 is rejected and ????1 is accepted. Then it can be calculated that the results show greater t_count and t_table 0 is rejected while 1 is accepted, so that there is a significant difference between student scores before and after using learning material from Android feature-based cartoon comics (66.33 > 40.73). shows that the last test is better than the previous test. The conclusion drawn is that interactive animated video media based on Android social research papers